Electromyographic thresholds are expressed in the double-poling test in cross-country skiers - Takeda, M.; Uda, S.; Kajiwara, W.; Nakano, H.; Horimoto, R.; Miyamoto, N.; Linnamo, V. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Since double-poling in cross-country skiing requires significant power during the poling motion, muscle endurance and high muscle power are essential. The upper body may rely more on muscle power and endurance than the lower body, where endurance is more critical [1]. It is known that there is a threshold in muscle activity, EMGT (electromyographic threshold), during incremental exercise [2]. Two break points (EMGT1 and EMGT2) are recognized for EMGT [3]. However, there are no reports on whether EMGT of muscles for double-poling is detected in the progressive test. This study investigates whether EMGT is observed in muscles for double poling in the progressive exercise test and, if so, how it is related to other physiological parameters.